Live Tissue Imaging Sheds Light on Cell Level Events During Ectodermal Organ Development - Mogollón, Isabel; Ahtiainen, Laura (Frontiers in Physiology, 2020)
Embryonic development of ectodermal organs involves a very dynamic range of cellular events and, therefore, requires advanced techniques to visualize them. Ectodermal organogenesis proceeds in well-defined sequential stages mediated by tissue interactions. Different ectodermal organs feature shared morphological characteristics, which are regulated by conserved and reiterative signaling pathways. A wealth of genetic information on the expression patterns and interactions of specific signaling pathways has accumulated over the years. However, the conventional developmental biology methods have mainly relied on two-dimensional tissue histological analyses at fixed time points limiting the possibilities to follow the processes in real time on a single cell resolution. This has complicated the interpretation of cause and effect relationships and mechanisms of the successive events. Whole-mount tissue live imaging approaches are now revealing how reshaping of the epithelial sheet for the initial placodal thickening, budding morphogenesis and beyond, involve coordinated four dimensional changes in cell shapes, well-orchestrated cell movements and specific cell proliferation and apoptosis patterns. It is becoming evident that the interpretation of the reiterative morphogenic signals takes place dynamically at the cellular level. Depending on the context, location, and timing they drive different cell fate choices and cellular interactions regulating a pattern of behaviors that ultimately defines organ shapes and sizes. Here we review how new tissue models, advances in 3D and live tissue imaging techniques have brought new understanding on the cell level behaviors that contribute to the highly dynamic stages of morphogenesis in teeth, hair and related ectodermal organs during development, and in dysplasia contexts.